1981
DOI: 10.1136/bjo.65.12.850
|View full text |Cite
|
Sign up to set email alerts
|

Altered cellular immunity and suppressor cell activity in patients with primary retinitis pigmentosa.

Abstract: SUMMARY A group of 54 patients with primary retinitis pigmentosa were studied and the following findings are described: response of lymphocytes to stimulation by phytohaemagglutinin (PHA); response of lymphocytes to stimulation by xenogenic retinal extract; distribution of T and T-active lymphoid populations; total suppressor activity induced by concanavalin-A (con-A). The results obtained showed a reduction in the response to PHA (p<005), a positive response of 26/45 (p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

1984
1984
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…Recent studies in RP evaluating immune responses to retinal antigens suggest the possibility that the immune system may contribute to the retinal degenerative process. 1-3 [5][6][7][8][9] Our results from the screening of sera to detect antibodies to retinal antigens indicate that autoimmune mechanisms are active in many patients with ocular degenerative disorders. A statistically significant (p<0-001) number of patients with both RP and non-RP eye disorders have circulating antibodies with activity directed towards retinal antigens as compared with normal controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in RP evaluating immune responses to retinal antigens suggest the possibility that the immune system may contribute to the retinal degenerative process. 1-3 [5][6][7][8][9] Our results from the screening of sera to detect antibodies to retinal antigens indicate that autoimmune mechanisms are active in many patients with ocular degenerative disorders. A statistically significant (p<0-001) number of patients with both RP and non-RP eye disorders have circulating antibodies with activity directed towards retinal antigens as compared with normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…6 Rocha Heredia et al showed sensitisation to retinal antigens in 26 out of 45 RP patients and presented evidence that lymphocytes from these patients also had a reduced response to phytohaemagglutinin in vitro and had diminished suppressor cell activity. 9 While autoimmune activity has been well recorded in RP patients, it is not known whether it is specific to certain types of RP or how commonly it occurs in other types of retinal degeneration and ocular disease. To determine the extent and specificity of immune mechanisms active in a number of retinal degenerative disorders two tests of immune function were evaluated in blood samples from patients with RP, patients with non-RP ocular disease, and normal control subjects.…”
mentioning
confidence: 99%
“…Die wichtigsten systemisch-immunologischen Befunde sind eine Erhohung der T-Helfer-Zellzahl und eine Erniedrigung der Suppressor-T-ZeIlzahl im Vergleich zu Gesunden (14,15,(18)(19)(20)(21). Von verschiedenen Arbeitsgruppen wurden bei Patienten mit Retinitis pigmentosa antiretinale Antikorper nachgewiesen, jedoch fand man diese in gleicher Häufigkeit auch bei anderen, insbesondere entzundlichen Vorder-und Hinterabschnitts-Erkrankungen (16,18,19).…”
Section: Charakteristischunclassified
“…Die Concanavalin-Astimulierte Suppressorzell-Aktivitat war erniedrigt. Sie interpretierten die gefundene Storung der zellulären Immunantwort als Zeichen für die Existenz elner Immunregulationsstorung bei primarer Retinits pigmentosa (20).…”
Section: Von Heckenlively Und Chant Wurden Beiunclassified
“…Due to its clinical and genetic heterogeneity, RP has limited therapeutic options. It has long been recognized that inflammation and immune responses are associated with RP, and this theme has recently gained increasing attention (4)(5)(6). Greater understanding of the molecular processes driving RP inflammation is expected to provide new therapeutic approaches independent of the genetic background.…”
mentioning
confidence: 99%